Moda Inclusiva: uma análise semiótica da representação da pessoa com deficiência no mercado de moda - Franco, Maíra Ferreira de Araújo (2020)
In our society, the appearance and the way of expressing oneself visually count a lot for a full social relationship. For people with disabilities, who have historically been marginalized from social life, fashion has a new meaning, constituting a possibility of breaking barriers and a means for inclusion. In recent years, the participation of this group in advertising campaigns has occurred exponentially and has been linked, mainly, to the increase of its presence in traditional media. The specific branch “inclusive fashion” covered a unique space and attention that was not known. This work aims to assess how the body of the person with a disability is portrayed by the media and advertising. The analysis is made in a comparative way between different reports extracted from the mainstream media, through discursive semiotics, prepared by Algirdas Julien Greimas and collaborators. In particular, we will work with the interaction regimes, the forms of otherness, the lifestyles and the sense of sociosemiotics developed by Landowski to understand how the relationship between a normative identity and minority alterities in the universe of fashion works. We hope, therefore, to contribute to the discussion about the processes of social inclusion in the world of fashion today and about which bodies are excluded from the debate on this topic. Keywords: semiotics; deficiency; media; interaction